Head and neck cancer patients' perceptions of quality of life and how it is affected by the disease and enteral tube feeding during treatment. (2nd October 2015) - Ehrsson, Ylva Tiblom; Sundberg, Kay; Laurell, Göran; Langius-Eklöf, Ann
Abstract: Aim . To explore individual quality of life in patients with head and neck cancer from diagnosis up to 3 months after termination of radiotherapy. Research questions: 1) Which areas in life are important to quality of life, and which are influenced by the disease and by having oral or enteral nutrition; and 2) Which areas in life are influenced by having a nasogastric feeding tube (NGT) or a percutaneous endoscopic gastrostomy (PEG) tube? Material and methods . Data were collected in 36 patients. Semi-structured interviews were conducted using an extended version of the Schedule for the Evaluation of Individual Quality of Life (SEIQoL) and analysed with content analysis. Results . Negative and positive experiences of quality of life in general were about relation to family, own health, and leisure activities. Negative impacts on physical, psychological, existential and social problems, but also positive experiences are described by the patients related to the disease. More than half expressed eating-related problems. Enteral nutrition entailed negative and positive experiences, and no greater variations were described by the patients with NGT or PEG tube. Overall, there were interindividual variations. Conclusions . The patients' perception of general or disease-related quality of life was not affected by whether they had enteral nutrition or not. From the patients' perspective neither of the two feeding tubes (NGT or PEG) was clearly in favour. We suggest that more studies are needed on how the choice of enteral feeding tube can be evidence-based, and incorporating the patients' perspective.